Práticas teatrais na educação: será que dá jogo? - Camelo, Natalia Beloti Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study investigates the use of theatrical practices as instrument of expression and manifestation of critical autonomous thinking. For this purpose, a field research in a public school in São Paulo with students attending the second year of high school was developed, in which meetings were proposed, which offered exposure to significant practices such as theater games, questioning and freedom of thought on their learning at school. Observing whether such practices dialogue with behaviors that manifest independent thoughts forms, through the rupture of standardized behaviors. The research presents a historical contextualization of the Art Education in Brazil, curriculum formation in the Brazilian educational system and concepts of Cultural Industry as well as their influence on behaviors and uniformed thoughts, especially in formation people, as in the case of adolescents in the research. Thus conjecture about the weakening of the free articulation of thinking ability of learners. And from this questioning, reflects how the theater can offer practical ways for adolescents perceive themselves as autonomous subject, and can act as agents of social transformation

O presente trabalho investiga a utilização de práticas teatrais como instrumento de expressão e manifestação do pensamento autônomo crítico. Para tanto, foi desenvolvida uma pesquisa de campo em uma escola estadual no Estado de São Paulo com alunos cursando o segundo ano do Ensino Médio. Foram propostos encontros que ofereceram exposição a práticas expressivas, como jogos teatrais, problematização e liberdade de pensar sobre o seu aprendizado na escola. Foi observado se tais práticas dialogam com comportamentos que manifestassem formas de pensamento independentes por meio da ruptura de comportamentos padronizados. A pesquisa apresenta uma contextualização histórica da ArteEducação no Brasil, a formação dos currículos no sistema educacional brasileiro e os conceitos da Indústria Cultural, bem como sua influência nos comportamentos e pensamentos uniformizados, sobretudo em pessoas em formação, como é o caso dos adolescentes da pesquisa. Deste modo, conjetura acerca do enfraquecimento da capacidade de articulação do livre pensar dos aprendizes. A partir desta problematização, reflete como as práticas teatrais podem oferecer caminhos para o adolescente se perceber como sujeito autônomo, e que possam atuar como agentes de transformação social
Keywords: Teatro na educação; Teatro; Educação do adolescente; Autonomia; Industria cultural; Theater